[Bożonarodzeniowa karta okolicznościowa ze Świętą Rodziną i robotnikami] . Christmas greeting card with Holly Family and workers (Polska, 1983)
Bi-fold greeting card with one panel with black and red print on white paper. Christmas greeting card contains a graphic image which represents the Holy Family and workers with banner "Christmas '83" written with Solidarity font.